Analisis Volatilitas Arus Kas, Volatilitas Penjualan, Besaran Akrual dan Pengaruhnya Terhadap Persistensi Laba Dengan Book Tax Differences Sebagai Variabel Moderating Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia - Samino Hendrianto; Nursimah Dara; Dyta Febriantine Pratikto (Jurnal Multidisiplin Madani, 2022)
The purpose of this study was to determine the effect of cash flow volatility, sales volatility and accruals on earnings persistence with book tax differences as moderating variables in consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2016-2020 period. The population of this study includes all consumer goods industrial companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 25 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results show that cash flow volatility has an effect on earnings persistence, sales volatility has an effect on earnings persistence, the amount of accruals has no effect on earnings persistence, book tax differences moderate the relationship between cash flow volatility and earnings persistence and cash flow volatility, sales volatility and the amount of accruals on persistence. earnings with book tax differences as the moderating variable.